ASPIRIN, NONSTEROID ANTIINFLAMMATION AS A PROPHYLAXIS IN REDUCING THE INCIDENCE OF PREECLAMPSIA: A SYSTEMATIC REVIEW - Petronella, Revynca (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Numerous randomized trials have reported the efficacy and safety of aspirin use during pregnancy and the variable effects of aspirin on the incidence of preeclampsia. Aim: This study aims to summarize and evaluate the efficacy of aspirin in preventing preeclampsia. Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, Google Scholar) and included articles published between 2019–2023. Duplicate publications, review articles, editorials, and incomplete articles were excluded. Results: Database searches identified a total of 92.832 articles. Of these, 100 articles passed the screening process, resulting in 22 articles for full-text assessment. Among them, 12 articles did not evaluate the outcome of interest. Hence, we found 10 appropriate studies included. Conclusion: Low-dose aspirin administration prior to 20 weeks of gestation reduces the incidence of preeclampsia significantly. However, additional research is required to investigate the long-term efficacy and safety of low-dose aspirin administration during pregnancy by assessing the long-term outcomes in expectant women and their infants.